Efek Peran Budaya dalam Proses Pembelajaran Organisasi di Pantura - Prayitno Prayitno; Tabrani Tabrani (Universitas Peradaban, 2017)
The main purpose of this paper is to investigate the effect of Cultural Role in Organizational Learning Process at Otto Bus Company in Pantura java area (Tegal, Brebes, Slawi). The purpose of this research is to know the effect of cultural role in Organizational Learning Process in Otto Bus Company in pantura area so that it has competitive advantage. Instrument used in this research is Value Survey Module 1994 (VSM 1994). This instrument is a revision of the previous questionnaire based on the question used in the original Hofstede research. A total of 125 questionnaires were distributed to all 10 companies. Each company received two copies of the questionnaire for its general manager and executive manager. Acceptable responses are accepted and analyzed. Researchers conducted 7 semi interviews to interpret and validate the results of the survey, from the results of research, researchers take the conclusion that the cultural dimensions of individualism and avoidance of uncertainty have a significant effect on organizational learning, where the area of pantura whose culture of individualism is still high into a competitive advantage and avoid the low uncertainty makes excellence separate community culture that supports organizational learning become more competitive.